Analysis of light quality and assemblage composition on diatom motility and accumulation rate. Issue 3 (2nd July 2016) - Cohn, Stanley A.; Dunbar, Samantha; Ragland, Ryan; Schulze, Jonathan; Suchar, Adam; Weiss, Jason; Wolske, Amanda
Abstract : The photosensitive nature of pennate diatom movement has long been observed, with cells being able to change the direction of their movement depending on the light conditions detected at the tips of the cells. However, much of this evidence is based on observations of cells in isolated, single-species culture, thus devoid of any information regarding inter-species interactions that might occur in more complex assemblages. In this study, we tested light-sensitive diatom motility responses (cell accumulation into light spots and high irradiation-induced direction change) in the absence and presence of other species. In the light spot accumulation assay, each species showed characteristic accumulation rates with regard to light irradiance, wavelength, and presence of other species. In mixed-species assemblages, the relative abundance of different species present in the light spot could be directly modified by changes in ambient light conditions. Diatom cells were also irradiated at their leading or trailing ends in the presence or absence of other diatom species to determine the effect of assemblage composition on high irradiance photo-responsiveness. While most multi-species combinations resulted in no significant change in the high irradiance response, Stauroneis phoenicenteron cells showed a significantly slower blue light stimulated direction change response, dependent on relative cell abundance in the presence of Craticula cuspidata . Our experiments thus indicate that the rate of irradiation-stimulated direction change and accumulation ability are not only species-specific and dependent on light wavelength and intensity, but can also be modulated by the presence of other diatom species.